Strategi Kepala Sekolah Dalam Peningkatan Mutu Pendidikan di TK IT Pendidikan Al Qur’an di Sentang Kecamatan Kisaran Timur Kabupaten Asahan - Widya Ayu Arinda; Sariana Marbun (Universitas Palan, 2023)
This study aims to describe the strategy of a kindergarten principal in improving the quality of education, from a leadership perspective, the role of the principal towards teachers and the management of the principal in the Integrated Islamic Kindergarten for Al-Qur'an Education in Sentang, Kisaran Timur District, Asahan District.The research method used in this study is a qualitative method with a qualitative descriptive approach. There were three subjects in this study, namely one school principal and two teaching teachers in the Integrated Islamic Kindergarten for Al-Quran Education. The data analysis technique used in this study is data reduction, data presentation, and drawing conclusions. The findings of this study indicate that the strategy of a school principal is seen from three aspects, namely: 1) Principal leadership, the head of the Integrated Islamic Kindergarten for Al-Qur'an Education, becomes a leader by learning to understand and learning to act professionally by dedicating oneself and being loyal to the school. 2) The role of the principal towards teachers in improving quality, the principal refers to improving good communication with teachers, students and school members. Meet the needs of teachers, both in fulfilling teaching and learning facilities and infrastructure. 3) Management of the principal of the school, carrying out the preparation, implementation of a program of school activities that have been designed to achieve school program goals in accordance with the school's vision, mission and goals that have been set.